(3YHbQjI GdUhQI h GdecGf (B:s (3GdJYHjQ(B- (3Gd`JChjd(B- (3GdfbO (B/s - (3YHO eSde,(BTahir Abid Muslim(3, WGgQs ((3YeGf (B:s (3OGQ GdTQhb ddfTQ h GdJhRjY ,s, 2002)
(3GfSGf GdUhQI gh Gdjhe GfSGf GNQ JJQcg GdTGTGJ eMedG HGdOgTI h GdGMSGS HGdLeGd h GdYLH dG fedc GRGAg Shi GdJYGWj h GdGfSLGe h Gj XeC gP G GdPj jLJGMfG aj Jdbj GdeRjO h GdeRjO ef GdUhQ GdQbejI Gfg GdfRhY GdNdGb dJYed eGcfI GdUhQ HdG GfJgGA h JJOab aj GdHjhJ h GdThGQY h GdGeGcf cdgGs
Keywords: (3Gdajdes; (3CfXeI GdJUhjQs; (3GdSeYj GdHUQjs; (3eYGdLI GdUhQs